Features of pre-scenography functioning in the ceremonial, ritual festive events of the Mordovians - Elena N. Antipkina; Olga N. Prokaeva (Финно-угорский мир, 2020)
Introduction. Ritual, ceremonial and festive events of the Mordovians represent a sphere of concentration and representation of spiritual-moral and value-oriented views of the people. They contain the origins of theatre and scenography as types of art. However, they cannot be considered as independent types of art in its modern meaning, as they used to exist in forms of theatricalization (pretheater) and pre-scenography. The subject of the article is the specifics of the functioning of pre-scenography in ceremonial, ritual and festive events of the Mordovians, as well as the disclosure of its main types: character type, determination of the place of action and game type. Materials and Methods. The theoretical materials are based on the research in the field of theatre and scenography. The reliability and academic validity of the research are ensured by the sociocultural approach, as well as by research methods, namely system-typological method, analytical method and interpretation method. Results and Discussion. Having studied the functioning of pre-scenography in ritual, three types of ceremonial and festive events of the Mordovians are revealed. The character type included a variety of components: metaphorical image, nature phenomena and objects, anthropomorphic and zoomorphic images, as well as objects of material culture. The next type determined the place of action which included everyday human environment, as well as production and household spaces. The game type implied conversion of performers of rituals and ceremonies into zoomorphic images, into various human (sometimes imaginary) characters through costumes, makeup and masks. Conclusion. Based on the analysis of the ritual, ceremonial and festive events of the Mordovians, a typology of pre-scenography is given, the special features of its functioning are determined.